KARYA TARI MAGERET PANDAN. POTRET AKTIFITAS BUDAYA MASYARAKAT DESA TENGANAN PEGRINGSINGAN DALAM SAJIAN SENI PERTUNJUKAN - Gunawan, I Gede Gusman Adhi (Widyadari: Jurnal Pendidikan, 2019)
This work aims to increase the creativity in the dance process, by presenting new ideas that are packaged into a performance art presentation and giving invitations to the community, to still maintain and preserve ancestral cultural heritage. The form of this work is the result of a historical, philosophical, and choreographic approach using observation and interview methods, by presenting creative dance performances. So that in the performance using the flow of Balinese dance performances in general, namely: Pengawit, Papeson, Pengawak, and Pengecet. This work is an implementation of the cultural activities of the Tenganan Pegringsingan community, namely Mageret Pandan, which is a ritual part of the Usaba Sambah ceremonial tradition which is poured into the choreography of a new dance creation. Mageret Pandan dance works are dance works that are rooted in historical, philosophical, and choreographic understanding and are then applied in the form of performance art.